(untitled) (Management and Connections Journal, 2023)
To seek success and survival in different markets, companies seek to cluster in what is called the local productive arrangement (APL). Therefore, the objective of this work was, through a systematic literature review, to identify the main characteristics used to qualify an APL. For this purpose, scientific articles published in the last 10 years in the Scopus database were searched. Articles in Portuguese and English were accepted in the areas relevant to the study. At the end of the searches, thirteen articles made up the sample of selected articles. After a complete reading of the articles, the respective objectives and characteristics of APL qualification were analyzed. It was concluded that the location quotient, the relative participation index, the Hirschman-Herfindahl index, the size of the companies, the number of employees and the level of cooperation are the main characteristics used to qualify an APL.